Lung metabolome of 1, 3-butadiene exposed Collaborative Cross mice reflects metabolic phenotype of human lung cancer. (November 2021) - Nellis, Mary; Caperton, Caitlin O.; Liu, Ken; Tran, ViLinh; Go, Young-Mi; Hallberg, Lance M.; Ameredes, Bill T.; Jones, Dean P.; Boysen, Gunnar
Abstract: 1, 3-Butadiene (BD) exposure is known to cause numerous adverse health effects, including cancer, in animals and humans. BD is metabolized to reactive epoxide intermediates, which are genotoxic, but it is not well know what other effects BD has on cellular metabolism. We examined the effects of exposure to BD on the mouse lung metabolome in the genetically heterogeneous collaborative cross outbred mouse model. Mice were exposed to 3 concentra-tions of BD for 10 days (2, 20, and 200 ppm), and lung tissues were analyzed using high-resolution mass spectrometry-based metabolomics. As compared to controls (0 ppm BD), BD had extensive effects on lung metabolism at all concentrations of exposure, including the lowest concentration of 2 ppm, as reflected by reprogramming of multiple metabolic pathways. Metabolites participating in glycolysis and the tricarboxylic acid cycle were elevated, with 8 out of 10 metabolites demonstrating a 2 to 8-fold increase, including the oncometabolite fumarate. Fatty acid levels, sphingosine, and sphinganine were decreased (2 to 8-fold), and fatty acyl-CoAs were significantly increased (16 to 31-fold), suggesting adjustments in lipid metabolism. Furthermore, metabolites involved in basic amino acid metabolism, steroid hormone metabolism, and nucleic acid metabolism were significantly altered. Overall, these changes mirror the metabolic alterations found in lung cancer cells, suggesting that very low doses of BD induce metabolic adaptations that may prevent or promote adverse health effects such as tumor formation.